Kantianism and Anti-Kantianism in Russian Revolutionary Thought - Chaly, Vadim (Con-Textos Kantianos. International Journal of Philosophy, 2018)
This paper restates and subjects to analysis the polemics in Russian pre-revolutionary Populist and Marxist thought that concerned Kant’s practical philosophy. In these polemics Kantian ideas influence and reinforce the Populist personalism and idealism, as well as Marxist revisionist reformism and moral universalism. Plekhanov, Lenin, and other Russian “orthodox Marxists” heavily criticize both trends. In addition, they generally view Kantianism as a “spiritual weapon” of the reactionary bourgeois thought. This results in a starkly anti-Kantian position of Soviet Marxism. In view of this the 1947 decision to preserve Kant’s tomb in Soviet Kaliningrad becomes something of an experimentum crucius that challenges the soundness of the theory.